The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3340/jkns.2019.0187
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Interferes with Autophagy and Affects Cell Survival in Irradiated Malignant Glioma Cells

Abstract: Objective : Radiation is known to induce autophagy in malignant glioma cells whether it is cytocidal or cytoprotective. Dexamethasone is frequently used to reduce tumor-associated brain edema, especially during radiation therapy. The purpose of the study was to determine whether and how dexamethasone affects autophagy in irradiated malignant glioma cells and to identify possible intervening molecular pathways. Methods : We prepared p53 mutant U373 and LN229 glioma cell lines, which varied by phosphatase and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
3
1
Order By: Relevance
“…As Dex did not interfere with GBM cell death induced by Ril (Figure 4), combined treatment with Ril and Dex could be beneficial for patients receiving Dex treatment for GBM oedema. Although previous research reported that Dex protects GBM cells from TMZ-induced apoptosis (22) and irradiation-induced autophagy (23), we detected no such negative effect of Dex in this study. This variable effect of Dex is potentially due to different experimental settings or cell lines.…”
Section: Discussioncontrasting
confidence: 99%
“…As Dex did not interfere with GBM cell death induced by Ril (Figure 4), combined treatment with Ril and Dex could be beneficial for patients receiving Dex treatment for GBM oedema. Although previous research reported that Dex protects GBM cells from TMZ-induced apoptosis (22) and irradiation-induced autophagy (23), we detected no such negative effect of Dex in this study. This variable effect of Dex is potentially due to different experimental settings or cell lines.…”
Section: Discussioncontrasting
confidence: 99%
“…Other research studies have however indicated that the concurrent administration of DEX with radiotherapy has been associated with a reduction in cell death among cancer cells. This suggests a potential role of DEX in promoting radioresistance [25] .…”
Section: Discussionmentioning
confidence: 88%
“…Dexamethasone (DEX) is commonly used together with chemotherapy against certain types of cancer [ 57 59 ] as well as for treating edema in children [ 60 ]. Previously, we showed that GR activation by glucocorticoids drives sympathetic neuronal differentiation in mice.…”
Section: Discussionmentioning
confidence: 99%